Employability of Graduates in India—Hard Realities - Khare, Mona (International Higher Education, 2018)
In the massified Indian higher education sector, the number of graduates seeking jobs is rapidly rising, but they often fall short of employers’ expectations due to poor “employability skills.” There are several distortions in the higher education system that are responsible for youth not being able to obtain and keep employment.